Efficacy of Combined Laparoscopic and Hysteroscopic Repair of Post-Cesarean Section Uterine Diverticulum: A Retrospective Analysis - Zhou, Lee Jaden Gil Yu Kang; Zhai, Jinguo; Han, Dong; Lin, Wanping; Gao, Xingcheng; Tang, Shiyan; Li, Cuilan; Mo, Xuetang (BioMed research international, 2016)
Background. Diverticulum, one of the long-term sequelae of cesarean section, can cause abnormal uterine bleeding and increase the risk of uterine scar rupture. In this study, we aimed to evaluate the efficacy of combined laparoscopic and hysteroscopic repair, a newly occurring method, treating post-cesarean section uterine scar diverticulum. Methods. Data relating to 40 patients with post-cesarean section uterine diverticulum who underwent combined laparoscopic and hysteroscopic repair were retrospectively analyzed. Preoperative clinical manifestations, size of uterine defects, thickness of the lower uterine segment (LUS), and duration of menstruation were compared with follow-up findings at 1, 3, and 6 months after surgery. Results. The average preoperative length and width of uterine diverticula and thickness of the lower uterine segment were recorded and analyzed. The average durations of menstruations at 1, 3, and 6 months after surgery were significantly shorter than the preoperative one ( p < 0.05 ), respectively. At 6 months after surgery, the overall success improvement rate of surgery was 90% (36/40). Three patients (3/40 = 7.5%) developed partial improvement, and 1/40 (2.5%) was lost to follow-up. Conclusions. Our findings showed that combined treatment with laparoscopy and hysteroscopy was an effective method for the repair of post-cesarean section uterine diverticulum.